2021
DOI: 10.1186/s12909-021-02490-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting paramedicine students’ learning about evidence‐based practice: a phenomenographic study

Abstract: Background Evidence-based practice is an important component of pre-service professional learning in medicine and allied health degrees, including new programmes in paramedicine. Despite substantial interest in this area, there is still a lack of clear understanding of how the skills and understandings needed to develop the capacity to apply evidence-based practice can best be learned. Evidence-based practice is often described as consisting of five steps: ask, acquire, appraise, apply and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[ 1 ] These factors have led EBP to gain significant importance in clinical practice, including physiotherapy. [ 2 ] However, the literature suggests that significant barriers have hindered the adoption of EBP by physiotherapists. [ 3 ] A systematic review found that while physiotherapists from Western countries mostly have a positive attitude toward EBP in daily patient care and decision making, yet a sizeable proportion rely on personal experience, educational courses, and in-service training for patient care decision making.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] These factors have led EBP to gain significant importance in clinical practice, including physiotherapy. [ 2 ] However, the literature suggests that significant barriers have hindered the adoption of EBP by physiotherapists. [ 3 ] A systematic review found that while physiotherapists from Western countries mostly have a positive attitude toward EBP in daily patient care and decision making, yet a sizeable proportion rely on personal experience, educational courses, and in-service training for patient care decision making.…”
Section: Introductionmentioning
confidence: 99%
“…(2019), who report that officers within frontline policing often know about EBP; however, the regular use in daily practice is limited, valuing instead the local tacit knowledge and experience of the “craft” of policing. In a similar way, Wilson et al . (2021), found that trainee paramedics gained the underpinning research skills during their studies, but the application to practice still required changes in both workplace attitudes and behaviours.…”
Section: Literature Review and Discussionmentioning
confidence: 75%
“…These research findings must be tempered though with those of Palmer et al (2019), who report that officers within frontline policing often know about EBP; however, the regular use in daily practice is limited, valuing instead the local tacit knowledge and experience of the "craft" of policing. In a similar way, Wilson et al (2021), found that trainee paramedics gained the underpinning research skills during their studies, but the application to practice still required changes in both workplace attitudes and behaviours. den Heyer (2023) suggests that one of the main barriers to the widespread adoption of EBP may be their immediate supervisors, who often act as gatekeepers to the sharing of research.…”
Section: Police Leaders: International Perspectivesmentioning
confidence: 84%
See 1 more Smart Citation
“…The subjects teaching and learning principles have thus become deeply-rooted in higher education curricular [European University Association, 2022]; but only in recent years has EBP begun to permeate the world of paramedic practice [Simpson et al, 2012]. Despite this paradigm, the impact of EBP may be limited in real-world practice because students (and quali ed staff) can struggle to implement these skills [Emms & Armitage, 2010;Warren, et al 2016] and whilst the concept may be considered favourable amongst graduates [Wilson et al 2021] a variety of barriers impact translation and application […”
mentioning
confidence: 99%